2007
DOI: 10.1080/14622200601078343
|View full text |Cite
|
Sign up to set email alerts
|

Western media's influence on Egyptian adolescents' smoking behavior: The mediating role of positive beliefs about smoking

Abstract: Western media has been implicated as an adolescent smoking risk factor in numerous Western studies, but little research has investigated that influence on adolescents from developing Arab countries. One such country is Egypt, which has the highest rate of smoking in the Arab world. An estimated 34% of Egyptians are daily smokers, 4% of whom are under the age 15 years and 0.6% of whom are under the age 10. The present study investigated the association between exposure and receptivity to Western media, positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 17 publications
2
21
1
Order By: Relevance
“…The Global Youth Tobacco Survey (GYTS) showed increasing numbers for never smokers susceptible to initiate smoking among Egyptian school children aged 13-15 years of both genders (El-Awa et al, 2010). There is also some evidence that Western media exposure is positively associated with smoking among Egyptian adolescents (Islam & Johnson, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The Global Youth Tobacco Survey (GYTS) showed increasing numbers for never smokers susceptible to initiate smoking among Egyptian school children aged 13-15 years of both genders (El-Awa et al, 2010). There is also some evidence that Western media exposure is positively associated with smoking among Egyptian adolescents (Islam & Johnson, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…PR-TTAURC and CSCS investigators and graduate students have produced over 140 peerreviewed publications, thus providing a wealth of information, which may contribute to future health promotion strategies. As an example, we have found that western media exposure and disposable income are associated with the adoption of certain health-risk behaviors such as smoking [30] and weight dissatisfaction among Chinese adolescents [31]. In our transnational comparisons, we have observed increasing rates of overweight/obesity among youth in more economically developed areas of China, such as the eastern coastal region and among Chinese immigrant populations in the USA [32,33].…”
Section: Adapting Western Theories To Chinese Conditions: the Case Ofmentioning
confidence: 72%
“…In Egypt significant effects were found only for boys (Islam & Johnson, 2007), in Germany (Hanewinkel & Sargent, 2007) and the United Kingdom (Waylen et al, 2011) similar effects as in the US were revealed, while studies from Scotland (Hunt et al, 2009(Hunt et al, , 2011 have produced conflicting results. A recent cross-cultural study in six European countries has found significant associations in the Netherlands, Poland, Italy, and Iceland, providing a strong case for the generalizability of these results to central Europe (Morgenstern et al, 2011(Morgenstern et al, , 2013.…”
Section: Differences In the Effect Of Exposure To Smoking In Movies Amentioning
confidence: 76%
“…This may be due to some of the following characteristics of the study: the sample of films was smaller than in most other studies, and contained only contemporary films, not recently popular films (for instance including the last five years). Consequently, the total number of smoking scenes that a respondent theoretically could be exposed to was small compared with the situation in studies using, for example, the Dartmond Medical School's design and data set (Sargent et al, 2001;Dalton et al, 2003;Islam & Johnson, 2007;Hunt et al, 2011, Morgenstern et al, 2011, where 50 titles are randomly selected from a larger sampling pool of 500-600 films. Our approach, with a fixed sample of 56 titles, may have underestimated possible underlying variance that might have been more adequately assessed by using a larger number of total smoking scenes.…”
Section: Linearitymentioning
confidence: 99%